Hailpad-based research: A bibliometric review - Palencia, Covadonga; Castro, Amaya; Giaiotti, Dario; Stel, Fulvio; Vinet, Freddy; Fraile, Roberto (Atmospheric research, 2009)
This paper is an overview of hailpad research from its origin until today using as a search criterion the bibliographic references on the subject in the Web of Science database (ISI). The search was carried out on 1st September 2008. Among the more than 3·10 7 scientific documents included in the Science Citation Index Expanded (SCI-EXPANDED) from 1945 to the present, the search engine identified 41 containing the word “hailpad⁎” (the asterisk is a wildcard for any letter or group of letters). The results have been analyzed according to various criteria: countries with hailpad networks or studies on hailpads; date of the first article; evolution of the number of articles per decade; concepts studied and research lines followed in each article; and finally, a bibliometric analysis of the journals where these articles have been published. It was found that 70% of the articles on hailpads were published in 2 journals: Journal of Applied Meteorology and Atmospheric Research. These two journals also concentrate most of the citations. The number of articles on hailpads and the documents that cite them have grown steadily, and it is expected to grow still further in the present decade if we take into account the trends found.